Phase IV Study Comparing Diurnal Glycemic Profile Following the Administration of 2 NPH Plus Regular Human DNA Recombinant Insulin Regimens in Type 1 Diabetes Mellitus (T1DM) Adult Patients - Feleder, E. C.; Yerino, G. A.; Halabe, E. K.; Tombazzi, J. L.; Farias, J. M. (Arzneimittelforschung, 2012)
Intensive insulin therapy (IIT) based on multiple daily injections of long plus rapid-acting insulin has been demonstrated to reduce mortality and morbidity associated with chronic hyperglycemia in T1DM patients. The objective of this study was to assess and compare the postprandial glycemic profile over a diurnal 12 h-period produced by the administration of a new NPH plus regular human DNA recombinant IIT (test regimen) relative to the reference IIT in T1DM patients. A phase IV, single-center, open-label, randomized, multiple-dose, balanced, cross-over study in 12 T1DM patients was conducted. Patients were assigned to receive either the test (Densulin® N (NPH) plus Densulin® R (regular),100 UI/ml, Denver Farma, Argentina) followed by the reference (InsulatardHM® (NPH) plus ActrapidHM®,100 UI/ml, Novo Nordisk Pharma Argentina) regimens or viceversa, according to a random sequence. Each treatment regimen consisted of 2 phases of an ambulatory run-in period of 7 days followed by 12 h confinement period. Blood glucose levels were measured. Glycemic profile was evaluated through glycemic plasma-concentration time curves, area under the time-concentration glycemic curves from basal to 2 h (GlyAUC0–2) and to 12 h (GlyAUC0–12) postprandial, and maximum glycemic postprandial concentration (GlyCmax). 12 hour glycemic concentration-time curves were similar for both test and reference regimens. Geometric least square means ratios Test/ref regimens and their 90% confidence interval for GlyAUC0–2, GlyAUC0–12 and GlyCmax were 94.33 (81.13–125.09), 107.75 (94.05–123.45) and 105 (92.89–118.68), respectively. Both regimens presented similar safety profile. This study demonstrated that the new human DNA recombinant NPH and regular insulin is equally effective to the reference regimen for postprandial diurnal glycemic profile.
Keywords: glycemic profile; NPH plus regular insulins; Type 1 Diabetes Mellitus